Freshmen [1919-1920] (1919)
A photograph of the Freshmen class of 1919. Image taken from page 30 (ua-pub_00000056_032) in the 1920 publication of the Polytechnic Journal. The full publication can be found here: https://digital.lib.calpoly.edu/rekl-27240